Effect of Topology on Photodynamic Sterilization of Porphyrinic Metal‐Organic Frameworks - Liu, Yao‐Yao; Chen, Li‐Jian; Zhao, Xu; Yan, Xiu‐Ping (Chemistry : a European journal, 2021)
Porphyrinic metal‐organic frameworks (MOFs) are promising photosensitizers due to the lack of self‐aggregation of porphyrin in aqueous solution. However, how the topology of porphyrinic MOFs affects the generation of singlet oxygen (1O2) is unclear. Here, the effect of the topology of porphyrinic MOFs on their photodynamic performance is reported. Four porphyrinic zirconium MOFs (MOF‐525, MOF‐545, PCN‐223 and PCN‐224 with different topologies: ftw, csq, shp and she, respectively) were selected to study the influence of topology on the photodynamic antibacterial performance. The 1O2 generation and the photodynamic antibacterial performance followed an decreasing order of MOF‐545>MOF‐525>PCN‐224>PCN‐223. The results reveal that the pore size, the distance between porphyrin, and the number of porphyrin per Zr6O8 cluster in MOFs greatly affected 1O2 generation. This work provides guidance for designing new MOFs for efficient photodynamic sterilization. Guide for designing photosensitizers: The effect of the topololgy of porphyrinic zirconium metal‐organic frameworks on 1O2 generation and photodynamic antibacterial performance was studied in four model MOFs. The number of porphyrin (TCPP) molecules per Zr6O8 cluster, the pore size and the distance between inter‐TCPP active sites, which are caused by variations in the MOF′s topology, play important roles in 1O2 generation.Thus, this work provides guidance for designing new MOFs as photosensitizers in photodynamic sterilization and therapy.